PENGARUH PROMOSI, KUALITAS DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ONEJAYA77 BUSANA (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
Society needs to dress up and dress is very advanced and follows the world fashion trends, sothat big people's desire to follow the development and style of dress according to the fashionnew trends. This study was to determine how much influence arising from each variable that ispromotion, quality, and price is in the independent variable.Based on partial analysis, it turns studies show that all the independent variables wereexamined in this study have a positive effect on the dependent variable, the variable is evidentin the promotion, quality and price have a positive influence on the dependent variable ispurchase decisions on ONeJaya77 Clothing Stores Bandar Lampung , Simultaneous testing, itturns out the results of the study prove that all the independent variables (Promotion, Quality,and Price) simultaneously have significant influence on the dependent variable, namely thepurchase of the store purchasing decisions ONeJaya77 clothing Bandar Lampung